2016
DOI: 10.1051/0004-6361/201629102
|View full text |Cite
|
Sign up to set email alerts
|

The Close AGN Reference Survey (CARS)

Abstract: We report the discovery that the known "changing look" AGN Mrk 1018 has changed spectral type for a second time. New VLT-MUSE data taken in 2015 as part of the Close AGN Reference Survey (CARS) shows that the AGN has returned to its original Seyfert 1.9 classification. The CARS sample is selected to contain only bright type 1 AGN, but Mrk 1018's broad emission lines and continuum, typical of type 1 AGN, have almost entirely disappeared. We use spectral fitting of the MUSE spectrum and previously available spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(157 citation statements)
references
References 31 publications
10
147
0
Order By: Relevance
“…This blue asymmetry was not present during the bright Type 1 AGN phase, and has likely appeared now because the red wing of Hα disappeared amid the dimming phase, as discussed in McElroy et al (2016). More importantly, we confirm that the prominent red wing asymmetry in Lyα and C iv is not present in Hα line only one month before the HST observations were taken.…”
Section: Broad Emission-line Variationssupporting
confidence: 79%
See 2 more Smart Citations
“…This blue asymmetry was not present during the bright Type 1 AGN phase, and has likely appeared now because the red wing of Hα disappeared amid the dimming phase, as discussed in McElroy et al (2016). More importantly, we confirm that the prominent red wing asymmetry in Lyα and C iv is not present in Hα line only one month before the HST observations were taken.…”
Section: Broad Emission-line Variationssupporting
confidence: 79%
“…Bennert et al (2011) found log (M BH /M ) = 8.15. The current L bol /L edd is around 0.03 (McElroy et al 2016). We note that because the broad-line region (BLR) of Mrk 1018 is currently not in an equilibrium or the virial factor has changed, recent M BH estimates are significantly different (e.g., current faint phase: log (M BH /M ) = 7.4; McElroy et al 2016).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on follow-up X-ray observations we rule out an obscuring-cloud event as the cause of the change of type again after 30 yr, as discovered in McElroy et al (2016). All observations, in particular the optical-UV SED, are consistent with a declining accretion rate of a geometrically thin, optically thick accretion disc.…”
Section: Discussionmentioning
confidence: 61%
“…These could be related to AGNs that change their BLR type and/or missing them (e.g. Tran 2001;Bianchi et al 2005;Zhang & Wang 2006;Kaastra et al 2014), which can occur even on short timescales (Storchi-Bergmann, Baldwin & Wilson 1993;Aretxaga 1999;Shappee et al 2014;Oknyansky et al 2016;McElroy et al 2016). Some peculiar types of AGNs could play a similar role, e.g.…”
Section: Subluminous Agn Flaring Scenariomentioning
confidence: 99%